Weed harrowing in wintwer cereal under semi-arid conditions - Pardo, G.=700 1 Cirujeda, A.; Aibar, J.; Cavero, J.; Zaragoza, C.
(En, Es)
Ilus., 30 ref.
Keywords: CEBADA; MALEZAS; ESCARDA MECANICA; RASTRA; TRIGO DURO; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH